Fluorinated phosphonate analogues of phenylalanine: Synthesis, X-ray and DFT studies - Joanna Kwiczak-Yiğitbaşı; Jean-Luc Pirat; David Virieux; Jean-Noël Volle; Agnieszka Janiak; Marcin Hoffmann; Donata Pluskota-Karwatka (Arabian Journal of Chemistry, 2020)
Due to their biological activity and structural analogy to corresponding α-amino acids, α-aminophosphonates and their fluorinated derivatives provide an important source for drug discovery. Therefore convenient access to this class of compounds is still desirable. Four series of novel phosphonate analogues of fluorinated phenylalanine containing variable number of fluorine atoms in different positions of the phenyl ring were synthesized and subjected to solid state characterization by single-crystal X-ray diffraction analysis, and to studies with the use of NMR, HRMS and DFT methods. Such an approach provided valuable information in regard to preferable conformation, hydrogen bonds and also weak intermolecular interactions present in the crystals investigated. As analogues of naturally occurring compounds, the obtained α-aminophosphonates have a big potential for biological activity. Formation of some indolinylphosphonates as minor products arisen from intramolecular SNAr reactions show that aminophosphonates exhibiting an electronically depleted aromatic group, and possessing a fluorine atom in ortho position of the phosphonoalkyl substituent may give an entrance to further derivatives that may exhibit entirely new properties. Keywords: Fluorinated aminophosphonates, Phenylalanine, Phosphonate analogues, DFT calculations, X-ray analysis, Hirshfeld surface analysis, Cluster analysis